Pembuatan Handsanitizer di Desa Grendeng Kecamatan Purwokerto Utara, Kabupaten Banyumas Sebagai Program KKN Tematik - Huwaida Yuko Salsabila; Rudy Wijaya; Muh. Sulaiman Dadiono (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
Hand sanitizer is one of the efforts to prevent the spread of Covid-19. As a solution, training was held to make hand sanitizer independently for residents of Grendeng Village. This training aims to facilitate access for the people of Grendeng Village, North Purwokerto District, Banyumas Regency to hand sanitizer. The methods used in the training were direct assistance and surveys. As a result, there was an increase in public awareness about the importance of using hand sanitizer and the ease of obtaining it after participating in the training.